Langton's turmite meets Lights Out. Issue 5 (29th December 2014) - Arangala, Crista
Abstract : The solution to the game of Lights Out and its many variants have been well studied. This article introduces Langton's turmite to the game of Lights Out and discusses when Langton's turmite can solve Lights Out on a torus. The article also explores the behavior of multiple Langton's turmites on a Lights Out on a torus. © 2014 Wiley Periodicals, Inc. Complexity 21: 155–161, 2016